Propionibacterium acnes isolated from lymph nodes of patients with sarcoidosis - de Brouwer, Bart; Veltkamp, Marcel; Wauters, Carla A; Grutters, Jan C; Janssen, Rob (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2015)
Propionibacterium acnes has been repeatedly suggested as a candidate causative agent of sarcoidosis. It is the only microorganism that has been isolated from sarcoid lesions by bacterial culture so far and this has been described in Japanese patients only. We report two non-Japanese patients in whom mediastinoscopy was performed in order to obtain lymph node tissue for histopathology, which was suggestive for sarcoidosis. Bacterial culture of these uncontaminated mediastinal lymph nodes revealed P. acnes in both patients. As shown in these two cases, P. acnes can be isolated from sterile biopsied sarcoid lymph nodes of non-Japanese patients and supports the belief that there is an etiologic link between P. acnes sarcoidosis. Further elucidation could provide an opening to novel strategies using antibiotics for treating sarcoidosis.